Predicting Melt Curves of Energetic Materials Using Molecular Models. Issue 8 (4th April 2022) - Tow, Garrett M.; Larentzos, James P.; Sellers, Michael S.; Lísal, Martin; Brennan, John K.
Abstract: In this work, the solid–liquid coexistence curves of classical fully flexible atomistic models of α‐RDX and β‐HMX were calculated using thermodynamically rigorous methodologies that identify where the free energy difference between the phases is zero. The free energy difference between each phase at a given state point was computed using the pseudosupercritical path (PSCP) method, and Gibbs–Helmholtz integration was used to evaluate the solid–liquid free energy difference as a function of temperature. This procedure was repeated for several pressures to determine points along the coexistence curve, which were then fit to the Simon–Glatzel functional form. While effective, this method is computationally expensive. An alternative approach is to compute the melting point at a single pressure via the PSCP method, and then use the Gibbs–Duhem integration technique to trace out the coexistence curve in a more computationally economical manner. Both approaches were used to determine the coexistence curve of α‐RDX. The Gibbs–Duhem integration method was shown to generate a melt curve that is in good agreement with the PSCP‐derived melt curve, while only costing ∼10 % of the computational resources used for the PSCP method. For α‐RDX, the predicted melting temperature increases significantly more for a given increase in pressure when compared to available experimental data. Abstract :